Recent trends in research on the role of cholesterol in leukemia: a bibliometric and visualization study - Lv, Huijuan; Lu, Ke; Wang, Ximing; Zhang, Yanfang; Zhuang, Mengqi; Li, Jing; Su, Keli; Gao, Wen (Frontiers in Immunology, 2025)
BackgroundCholesterol metabolism significantly impacts leukemia pathophysiology, affecting tumor cell survival, proliferation, and treatment resistance. This study employs bibliometric analysis and visualization techniques to investigate research trends regarding cholesterol in leukemia and identify key hotspots.MethodsA systematic search of the Web of Science Core Collection was performed for literature published from 1980 to 2024 using the keywords “cholesterol” and “leukemia,” yielding 1,220 articles. Bibliometric tools like VOSviewer and CiteSpace were utilized for visualizing citation networks and thematic clusters.ResultsThe analysis comprised 1,220 publications produced by 6,771 researchers across 1,756 institutions in 68 countries, published in 576 journals with 5,903 unique keywords. Publication output demonstrated a significant rise from 1980 to 2024, peaking in 2022. The United States led in total publications (381) and citations (40,462), followed by China (137 articles) and Japan (102). Notably, U.S. publications had lower average citations than those from Germany and Brazil. Key institutions included the University of São Paulo, Medical College of Wisconsin, and National Cancer Institute, with prominent authors such as Maranhao Raul C. and Girotti Albert W. The journal Cancer Research was the most prolific, while Blood had the highest citation frequency. Major research areas encompassed molecular biology, immunology, and medicine, focusing on the cholesterol-leukemia link. Keyword co-occurrence and co-citation analyses reveal increasing interest in topics like STAT3, multidrug resistance, and treatment interactions. These insights suggest crucial areas for further research.DiscussionOur findings emphasize cholesterol’s significance in leukemia, indicating its potential as a therapeutic target. Further exploration at the intersection of cholesterol metabolism and leukemia requires multidisciplinary collaboration.ConclusionThis bibliometric study delineates the evolving research landscape on cholesterol’s role in leukemia, pinpointing emerging trends and future research directions to inform effective therapeutic strategies.